Adolescents et délinquance sexuelle - Laforest, Suzette; Paradis, Richard (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1990)
Our work with young offenders at the Quebec Social Service Centre has led us to intervene more and more frequently among adolescents for sex-related offences. We felt the need, therefore, to know more about the matter in order to be able to answer the needs of this clientèle more realistically. Thus we conceived of group therapy centred on the psychosexual development of these adolescents, along with complementary individual treatment. A first experiment was undertaken in the spring of 1989. The results encourage us to pursue this type of treatment, always adjusting it to the needs underlying the behaviour of these adolescents. It must be pointed out that the data and the thinking contained in this article are drawn from our practice. It is as social workers that we deal with this problem.